Assessed, student-led dialogic interaction: a Bakhtinian analysis of a case study of undergraduate history seminars - Bentley, Sarah (Sally) Ann (2010)
A Bakhtinian theoretical framework throws fresh light on higher education assessment, dialogue and classroom dynamics, demonstrating that assessed, student-led seminars can have a powerfully positive effect on student learning.